MANAJEMEN PENYIARAN SERTA PENGEMBANGAN RADIO DAN TELEVISI: RADIO AND TELEVISION DEVELOPMENT BROADCASTING MANAGEMENT - Winda Kustiawan; Nadya Syakilah; Tasya Salsabila; Arif Indra Hasan; Ari Oldwin Sitorus (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2022)
Broadcasting management is intended so that the media and the broadcasting industry can maximize the purpose of broadcasting itself, namely providing information, providing education and providing entertainment to the public. Through broadcasting management, it is hoped that the broadcasting industries will be able to actualize each program properly. Radio and television, which are included as public press media, must also experience development in terms of operations, production or programs that will be conveyed to the public. With the presence of development and management, all problems that will hinder the smooth running of the program will be resolved. The approaches that must be taken are also very varied, for example the approach by means of comparative study methods or upgrading in terms of human resources or facilities that will be used to support the smooth running of the program, especially radio and television programs.